Alfuzosin for the medical treatment of benign prostatic hyperplasia and lower urinary tract symptoms: a systematic review of the literature and narrative synthesis. (April 2021) - Mari, Andrea; Antonelli, Alessandro; Cindolo, Luca; Fusco, Ferdinando; Minervini, Andrea; De Nunzio, Cosimo
Background: Lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH) are a bothersome frequent symptom in adult males. This systematic review analyzed the available evidence on the pharmacokinetic and pharmacodynamic features of alfuzosin, and its clinical efficacy both as monotherapy and in combination with other drugs for the treatment of male LUTS/BPH. Methods: A systematic review of the last 10 years was performed using the MEDLINE, EMBASE and Cochrane libraries in March 2020. The protocol for this systematic review was registered on PROSPERO (Central Registration Depository: CRD42020136120) and is available in full on the University of York website. Results: Alfuzosin is a quinazoline derivative and, although a nonspecific α1-blocker, exhibits a selective concentration in the prostate compared with plasma in patients with BPH. Three registration trials assessed the safety and efficacy of alfuzosin. The 10 mg daily formulation has a three-layered matrix containing the active substance between two inactive coats allowing a drug release over 20 h. Alfuzosin showed high tolerability, few vasodilatory effects and a low rate of ejaculation disorders over older alpha-blocking compounds thanks to the high uroselectivity of alfuzosin and its preferential concentration at urinary level. Six randomized clinical trials (RCTs) assessed efficacy and safety of alfuzosin versus other alpha-blockers ± placebo: three studies comparing with tamsulosin, one with doxazosin, and two with silodosin or tamsulosin. One RCT investigated the clinical outcomes of alfuzosin with finasteride, two with propiverine and two with phosphodiesterase-5 inhibitors. Conclusions: Alfuzosin is an effective drug for the treatment of LUTS/BPH, with a lower rate of sexual disorders compared with other alpha-blockers. Alfuzosin is also safe with low adverse events in case of concomitant antihypertensive therapy and in patients with cardiovascular morbidity. Safety and efficacy of alfuzosin has been reported also in case of combination therapy with antimuscarinic agents and PDE5i.